Three planets around HD 27894: a close-in pair with a 2:1 period ratio and an eccentric Jovian planet at 5.4 AU - Trifonov, Trifon; Reffert, Sabine; Brems, Stefan S. (Arxiv, 2017)
Aims. Our new program with HARPS aims to detect mean motion resonant planetary systems around stars which were previously reported to have a single bona fide planet, often based only on sparse radial velocity data. Methods. Archival and new HARPS radial velocities for the K2V star HD 27894 were combined and fitted with a three-planet self-consistent dynamical model. The best-fit orbit was tested for long-term stability. Results. We find clear evidence that HD 27894 is hosting at least three massive planets. In addition to the already known Jovian planet with a period $P_{\rm b}$ $≈$ 18 days we discover a Saturn-mass planet with $P_{\rm c}$ $≈$ 36 days, likely in a 2:1 mean motion resonance with the first planet, and a cold massive planet ($≈$ 5.3 $M_{Jup}$) with a period $P_{\rm d}$ $≈$ 5170 days on a moderately eccentric orbit (
Gesehen am 11.10.2017